A Novel Technique of Power Flow Control in Transmission Lines Using Interline Power Flow Control - Pankaj Aswal; Suyash Kumar Singh; Apurv Thakur; Kshitij Gaur (Institute of Advanced Engineering and Science, 2016)
The interline power flow control (IPFC) is the flexible AC transmission system controller (FACTS) came into accountability to control the flow of power in multiple line transmission system. The following paper demonstrates the IPFC modelling using Matlab Simulink. Power flow calculations has been made using Gauss-Seidel Method. Optimization of power in terms of real and reactive power flow is achieved by comparing the actual calculated term and the predicted value.